2020
DOI: 10.3390/en13225958
|View full text |Cite
|
Sign up to set email alerts
|

Winter Thermal Comfort and Perceived Air Quality: A Case Study of Primary Schools in Severe Cold Regions in China

Abstract: In Northeast China, most classrooms in primary and secondary schools still use natural ventilation during cold days in winter. This study investigated the thermal comfort and the perceived air quality of children in primary schools in severe cold regions in China. Field measurements were conducted in four typical primary classrooms in two naturally ventilated teaching buildings in the winter of 2016 in the provincial city of Shenyang. Six field surveys were distributed to 141 primary students aged 8 to 11, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…They have been extensively researched in the literature in different types of buildings, such as nursing homes (Forcada et al, 2021) and educational buildings (B. Yang et al, 2018;Jiang et al, 2018a;Haddad, Osmond and King, 2019;Jindal, 2019;Heracleous and Michael, 2020;Ma et al, 2020;Alonso et al, 2021;Aparicio-Ruiz et al, 2021;Kükrer and Eskin, 2021a;Lamberti et al, 2021;Oh and Song, 2021b;Rodríguez, Coronado and Medina, 2021;Shrestha et al, 2021;Taylor, Brown and Rim, 2021a) health care buildings (Bouzidi et al, 2021) and places of worship (Vella et al, 2021). Although this adaptive approach works better in naturally ventilated buildings, it fails to include some important aspects of the traditional thermal comfort model (Halawa and Van Hoof, 2012).…”
Section: Thermal Comfort Model Developmentmentioning
confidence: 99%
“…They have been extensively researched in the literature in different types of buildings, such as nursing homes (Forcada et al, 2021) and educational buildings (B. Yang et al, 2018;Jiang et al, 2018a;Haddad, Osmond and King, 2019;Jindal, 2019;Heracleous and Michael, 2020;Ma et al, 2020;Alonso et al, 2021;Aparicio-Ruiz et al, 2021;Kükrer and Eskin, 2021a;Lamberti et al, 2021;Oh and Song, 2021b;Rodríguez, Coronado and Medina, 2021;Shrestha et al, 2021;Taylor, Brown and Rim, 2021a) health care buildings (Bouzidi et al, 2021) and places of worship (Vella et al, 2021). Although this adaptive approach works better in naturally ventilated buildings, it fails to include some important aspects of the traditional thermal comfort model (Halawa and Van Hoof, 2012).…”
Section: Thermal Comfort Model Developmentmentioning
confidence: 99%
“…The most frequent finding in both NV and AC classrooms is that applying existing adult-specific thermal comfort benchmarks and clothing values, is not suitable for primary school students [9,36,76,79,81]. Children seem to find the classroom temperature relatively hot and prefer lower temperatures than adults, even in winters [9,76,[79][80][81]. Furthermore, it has been demonstrated that thermo-neutrality, or neutral temperature sensations, is a poor indicator of children's thermal comfort [76,79,81].…”
Section: Adaptive Opportunities For Students In Classroomsmentioning
confidence: 99%
“…IAQ has an important impact on human health, although a large number of studies have focused on residential 25 , 26 , office buildings 27 , 28 education in different climate zones buildings 29 , 30 and IAQ in large commercial buildings 31 , 32 but there are fewer relevant studies focusing on sports buildings. In China, stadiums will be built in strict accordance with the design code for sports building JGJ 21-2003 and other national standards for design, and after the stadiums are put into use, with the increase in the number of years of use, the status of IAQ in the pavilion?…”
Section: Introductionmentioning
confidence: 99%